Controlling Cancer Cell Behavior by Improving the Stiffness of Gastric Tissue-Decellularized ECM Bioink With Cellulose Nanoparticles - Kim, Jisoo; Jang, Jinah; Cho, Dong-Woo (Frontiers in Bioengineering and Biotechnology, 2021)
A physiologically relevant tumor microenvironment is favorable for the progression and growth of gastric cancer cells. Several biomaterials engineering studies have investigated three-dimensional (3D) cultures to simulate tumor-specific conditions similar to in vivo environments; however, the implementation remains limited because of challenges in outlining the biochemical and biophysical characteristics of the gastric cancer microenvironment. In this study, we developed a 3D cell printing-based gastric cancer model using a combination of gastric tissue-specific bioinks and cellulose nanoparticles (CN) to provide adequate stiffness to gastric cancer cells. To create a 3D gastric tissue-specific microenvironment, we successfully developed the decellularization process of a gastric tissue-derived decellularized extracellular matrix (g-dECM) bioink and investigated the effect of the g-dECM bioink on promoting the aggressiveness of gastric cancer cells using histological and genetic validation methods. We found that incorporating CN improves the mechanical properties of the matrix, which supports the progression of gastric cancer. These mechanical properties are distinguishable characteristics that can facilitate the development of an in vitro gastric cancer model. Further, the CN-added g-dECM bioink was used to print a variety of free-standing 3D shapes including gastric rugae. These results indicate that the proposed model can be used to develop a physiologically relevant gastric cancer system that can be used in future preclinical trials.